On the role of value systems and reciprocity in collaborative environments - Abreu, António (2020)
The establishment of a common value system is an important element for the sustainability of collaborative networks. This paper discusses the role of value systems in the VO breeding environment when the promotion of the cooperation is based on reciprocity mechanism. Some scenarios are included in the discussion and illustrations are given based on data from real networks.